The Discovery of NEW Golobe and Its Amazing Healing System - Hendry Izaac Elim (Faculty of Mathematics and Natural Sciences, University of Pattimura, 2019)
Here, one reported a discovery of new golobe or a novel kind of zingiberaceae fruit in a forest of Layeni village located in Teon-Nila-Serua (TNS) district of Seram island, Maluku province, Indonesia in the late afternoon on 25th February 2019. The new golobe is very different from the four (4) formal types of golobe fruits studied before. After intense prompt investigations, the new golobe was named as Elim alliacea based on the taller tree and fruit hard skin structures as well as its unique taste. Furthermore, the healing system of the golobe was identified to be very excellence in handling toxic instantly. This discovery suggests a prominent potential of this fruit as multitasking healing herbal medicine for future complicated deceases on earth.